"Impossible objects" in a life‐threatening crisis: A study of patients suffering from adverse childhood experiences and myocardial infarction. (7th October 2020) - Petersen, Anke; Ruettner, Barbara; Kaiser, Paul; Richardt, Gert; Goetzmann, Lutz
Abstract: Adverse childhood experiences (ACE) are considered as risk factors for myocardial infarction (MI). It is unknown how ACE affects the experience of MI patients. In a qualitative study, a total of 25 MI patients with and without ACE (ACE: n  = 20, N‐ACE: n  = 5) were asked about their biography and the heart attack. A content analysis was carried out. Inter‐rater reliability showed a good to complete agreement. ACE patients reported primarily on experiences of loss and violence in their childhood and youth. ACE patients tend to dissimulate symptoms, and there is a hazardous latency of seeking medical help. The potential helpers are experienced as "impossible objects." Primary care providers should pay special attention to the situation of ACE patients and be aware of their countertransference, that is, that the condition is not recognized as seriously as it should be.